Implementasi Pendekatan Arstiektur Futuristik pada Perancangan Stasiun Pengisian Kendaraan Listrik Umum di Kota Makassar - Nuh Apriansyah, Muhammad; AS, Zulkarnain; Oktawati, Andi Eka (TIMPALAJA : Architecture Student Journals, 2026)
infrastructure, particularly in major cities such as Makassar, which has strong potential to support electric vehicle growth in Eastern Indonesia. However, the availability of Public Electric Vehicle Charging Stations (PEVCS) still needs to be improved to meet users’ functional, comfortable, and sustainable mobility needs. This study aims to design an SPKLU in Makassar City using a futuristic architectural approach, not only as a technical charging facility but also as a building with aesthetic value, strong visual identity, and supporting facilities for users. The method used is a descriptive, qualitative approach with an architectural design focus, conducted through literature reviews, site observation, interviews, spatial needs analysis, circulation analysis, and precedent studies of similar buildings. The design results show that a futuristic architectural approach is applied through dynamic building forms, the use of innovative materials such as stainless steel cladding and recycled plastic sheeting, smart glass applications, charging parking sensor systems, and the utilization of solar panels. The design also provides supporting facilities, including waiting areas, cafes, restaurants, minimarkets, showrooms, workshops, car wash areas, prayer rooms, ATM centers, green open spaces, and gazebos. Therefore, the proposed SPKLU is expected to become a modern, comfortable, and technology-adaptive charging facility that supports Makassar’s image as a sustainable city.